Degendering leadership in higher education - Katuna, Barret (Great debates in higher education., 2019)
Binary gendered leadership definitions are threatening to leaders whose styles do not match these narrow understandings, and do not leave room for trans, non-binary, and intersex leaders who do not fit within this binary that does not predict leadership styles. Through 34 interviews with women and men serving as presidents, deans, and provosts at some of the United States' top colleges and universities, this book explores what degendered leadership looks like in an academic setting. Higher educational settings have seen more women in leadership roles than in corporate and governmental settings, making this a prime setting for the study of the intersection of gender and leadership. Through interview analysis, the author addresses the following questions: What role does gender play in the narratives of women and men leaders? How might leaders' gendering of leadership reproduce gender stereotypes? What strategies might leaders and institutions of higher education use to degender leadership? and What might degendered leadership look like? This timely and important book creates a path for inspired, talented, and qualified leadership that is not reduced to gender norms and stereotypes. Institutions that wish to see leadership diversity and that strive toward creating inclusive academic communities need to pay attention to leadership expectations associated with stereotypes that encompass all identities including race, sexuality, ethnicity, age, and religion. This book is a tool for promoting leadership diversity.